The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3846/16111699.2017.1400460
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Digital Media and Impact of Customer Attitude and Technology on Brand Awareness: Evidence From the South Asian Countries

Abstract: The purpose of this study is to investigate the role of interactive digital media channels such as social media, email marketing, and mobile marketing in creating the brand awareness. We have assimilated three behavioral factors including perceived value, trust, and word of mouth as mediating factors, and the Internet and smartphone as moderating variable. Total 2565 responses have been taken to investigate the role of digital media channels, and impact of mediating and moderating variables on the brand awaren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 38 publications
3
53
0
4
Order By: Relevance
“…Another study was conducted on the compulsive use of smartphones and it was demonstrated that addiction to smartphones increases mental stress and reduces concentration among students [102][103][104]. Smartphone addiction plays a moderating role in the association of smartphone functions, and student academic performance in universities [12,105,106]. It is therefore hypothesized that:…”
Section: Addiction As a Moderatormentioning
confidence: 99%
“…Another study was conducted on the compulsive use of smartphones and it was demonstrated that addiction to smartphones increases mental stress and reduces concentration among students [102][103][104]. Smartphone addiction plays a moderating role in the association of smartphone functions, and student academic performance in universities [12,105,106]. It is therefore hypothesized that:…”
Section: Addiction As a Moderatormentioning
confidence: 99%
“…Alasan yang kedua dapat dilihat dari table satistik, responden yang menjawab "setuju" pada indikator variabel kepercayaan dan kesadaran merek. Hasil yang sama juga menunjukkan adanya hubungan yang signifikan antara kepercayaan dan kesadaran merek oleh Ahmed et al (2017), ISSN : 2088-1231 E-ISSN: 2460-5328 DOI: dx.doi.org/10.22441/mix.2020.v10i1.007 Disfani (2016), Gholami (2017), Lee dan Jee (2015), Martin dan Strong (2016), Mudzakir dan Nurfarida (2016), Pramudya et al (2017), Wang dan Lee (2016).…”
Section: Keterhubungan Antar Variabelunclassified
“…Terdapat keterhubungan positif antara kepercayaan dan persepsi kualitas. Penelitian sebelumnya yang berkaitan dengan kepercayaan dan kesadaran merek adalah,Ahmed et al (2017),Disfani (2016),Gholami (2017),Lee dan Jee (2015),Martin dan Strong (2016), Mudzakir dan Nurfarida (2016), Pramudya et al(2017),Wang dan Lee (2016). Maka terbentuklah hipotesis keempat yaitu: H4: Terdapat keterhubungan positif antara kepercayaan dan kesadaran merek konsumen akan keberadaan merek sudah mampu memberikan persepsi atas kualitas produk dari salah satu merek yang mereka gunakan(Eliasari dan Sukaatmaja 2017, 6624).…”
unclassified
“…Scientists suggest a strong relationship between information quality, system quality, service quality, and technology acceptance model. Furthermore, this study has extended the technology acceptance model with trust, because trust is an essential factor in the relationship of three qualities and technology acceptance model (Ghazizadeh et al, 2012;Yang et al, 2015), taking in to account recent studies in consumer behaviour (Ahmed, Vveinhardt, & Streimikiene, 2017;Cachero-Martinez & Vazquez-Casielles, 2017;Debkowska, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%